Simultaneous design of the topology and the build orientation of Wire-and-Arc Additively Manufactured structural elements. (1st January 2021) - Bruggi, Matteo; Laghi, Vittoria; Trombetti, Tomaso
Highlights: A tool to design structural elements for Wire-and-Arc Additive Manufacturing is presented. Topology and print direction are simultaneously optimized for lightweight design. Experimental data are processed to characterize an orthotropic model of the printed alloy. Shape variations arise from changes in the printing orientation. Optimal layouts are found in conjunction with non-trivial build directions. Abstract: Wire-and-Arc Additive Manufacturing (WAAM) has been recently adopted to create innovative structural forms and architectural shapes. As shown by few experimental investigations, the layer-by-layer deposition induces a remarkable anisotropy in the elastic response of the WAAM-produced alloys. A suitable topology optimization technique is implemented to account for this peculiar behavior of the material, which is generally disregarded in design tools that are conceived for traditional manufacturing. First, an orthotropic material model is derived from the data of an experimental investigation that was recently performed on alloys made with 308LSi stainless steel wire feed. Then, an optimization procedure is implemented that exploits, as design variables, not only the density field of an orthotropic material phase, but also the orientation of the symmetry axes of such material with respect to a reference frame (i.e. the printing direction used to build the whole structural element). Minimum weight problems with displacement constraints are solved to find optimal solutions that are compared to those achieved by performing topology optimization with (i) isotropic stainless steel or with (ii) the WAAM-produced alloy for prescribed orientations. Numerical simulations assess that the printing direction remarkably affects the stiffness of the optimal layouts, as well as their topology.